Nutritional composition of fruits selected by long-tailed Macaques (Macaca fascicularis) in Kuala Selangor, Malaysia - Norazila Kassim; Kamarul Hambali; Aainaa Amir (Universiti Sains Malaysia, 2017)
Proximate analysis of twelve species of fruits commonly consumed by longtailed macaques (Macaca fascicularis), i.e., Arenga pinnata, Areca catechu, Terminalia catappa, Elaeis guineensis, Lagerstroemia tomentosa, Mangifera indica, Cascabela thevetia, Muntingia calabura, Musa sp., Artocarpus heterophyllus, Ficus tinctoria ssp. gibbosa and Ficus microcarpa, was conducted with the specific objective to determine the nutritional composition of the foodstuffs of long-tailed macaques. The results showed the following order of nutrients: fibre, protein, fat and ash. Based on the results of the chemical analysis, the highest percentage of fibre content (52.7%), protein (9.9%), fat (77.2%) and ash (8.5%) were found in A. catechu, T. catappa, E. guineensis and C. thevetia, respectively. The nutrient composition of these twelve fruit species was found to differ (ANOVA test: crude protein, F (11,24) = 87.978, p < 0.05; crude fibre, F (11,24) = 28.886, p < 0.05; crude fat, F (11,24) = 2081.396, p < 0.05 and ash, F (11,24) = 41.011, p < 0.05). Fibre was found in the highest amount among the four types of nutrients studied. Here, A. catechu had the highest relative fibre content of all tested fruits, E. guineensis had the highest fat content, T. catappa had the highest protein content, and the total mineral content was highest in C. thevetia